ANGI-09. BEVACIZUMAB IN ATYPICAL AND ANAPLASTIC MENINGIOMAS: THE BEMEN STUDY. (14th November 2022) - Cerretti, Giulia; Bosio, Alberto; Maccari, Marta; Padovan, Marta; Caccese, Mario; Zagonel, Vittorina; Lombardi, Giuseppe
Abstract: BACKGROUND: the current standard to treat meningiomas can include surgical resection and radiotherapy. Despite the high rate of relapse no systemic treatment is indicated. Few data are available regarding the effectiveness of bevacizumab (BEV) in this setting. We performed a retrospective analysis investigating the efficacy and safety of BEV in meningioma patients relapsed after receiving surgery and radiotherapy. Gene mutations were also collected. Material and METHODS: we analyzed pts treated with off-label BEV from Jul 2019 to Feb 2022. Inclusion criteria were diagnosis of grade 2-3 meningioma, previous treatment with surgery and radiotherapy, no indication to further surgery or reirradiation, absence of contraindications to the use of BEV. Data were estrapolated from clinical records. RESULTS: Median follow up was 13 months (3-30 range). 26 pts were enrolled. Median age was 68 ys (29-84); male pts were 16 (61%);61% (16 pts) with atypical meningioma, 38.5% (10 pts) with anaplastic meningioma; 27% (7 pts) underwent 2 or more surgeries; 58% had 2 or more RT treatments; 96.1% (25 pts) received < 2 previous lines of systemic treatment. 61% of patients (16 pts) had NGS analyses available; 62% (10 pts) had NF2 mutations (1 pt had a confirmed diagnosis of neurofibromatosis type 2), 23% (6 pts) CDKN2A/2B deletion, 11% (3 pts) PTEN mutation. OS rate was 82% and 62% at 6 and 12 months respectively; 6 months PFS rate was 83%. The DCR was 71% and the ORR was 19%. Median PFS and OS weren't reached. 19% (5 pts) experienced CTCAE grade 1 or 2 toxicity, mainly hypertension. CONCLUSION: BEV showed very promising activity in recurrent grade 2-3 meningioma. The treatment was well tolerated. BEV should be considered an optimal therapeutic option in this setting of meningioma patients. The NGS results might be useful in identifying targetable mutations in case of further recurrence.